Microbiological patterns of endophthalmitis in a tertiary level hospital of Kathmandu, Nepal - Shrestha, Smita; Manandhar, Anu (Nepalese Journal of Ophthalmology, 2020)
Introduction: Endophthalmitis is a serious ocular infection that can result in blindness and therefore is a major ophthalmic concern. The study was conducted to find out the microbial etiology in clinically diagnosed cases of endophthalmitis and to determine the antibacterial susceptibilities of bacterial isolates in vitro. Materials and methods: A retrospective analysis was carried out of all patients presenting between 15th January 2012 to 15th January 2013 with clinically diagnosed Endophthalmitis at Tilganga Institute of Ophthalmology (TIO). Intraocular specimens (aqueous or vitreous fluids) were collected from 102 patients. Along with intraocular aspirates, blood and urine specimens, chest X-ray from endogenous endophthalmitis and corneal scrapes from corneal ulcer leading to endophthalmitis were also collected. The intraocular specimens were then subjected to microbiological evaluation. Antibiotic susceptibility of isolates were determined for different ocular antibiotics using the Kirby-Bauer disk-diffusion test. Results: Samples from 102 patients diagnosed with endophthalmitis underwent microbiological analysis, of which culture positive 34(33.33%). Out of 34, 29 (85.29%) had bacterial growth and the remaining 5 (14.70%) had fungal growth. Most of them (40.8%) were secondary to cataract surgery(postoperative). A total of 29 bacterial culture reports, 72.41% were gram-positive and 27.58% were gram-negative. Streptococcus pneumoniae (37.93%) was the most frequently isolated organism. The antimicrobial sensitivity for isolates was as follows: Ofloxacin - 86.2%, Chloramphenicol - 82.75%,Cefazolin- 82.7%, Gentamicin - 75.8%, Ceftazidime - 58.6%, Amikacin - 55.17% and Vancomycin - 51.7%. Conclusion: The data highlights low culture positivity and a predominance of gram positive bacteria as the major causes of infectious endophthalmitis, usually following cataract surgery. The most common isolate was Streptococcus pneumoniae. Ofloxacin and Chloramphenicol demonstrated greatest efficacy against these bacterial isolates.